USING IN SITU-PRODUCED 10BE TO QUANTIFY ACTIVE TECTONICS IN THE GURVAN BOGD MOUNTAIN RANGE (GOBI-ALTAY, MONGOLIA) - Ritz J.-F.; Vassallo R.; Braucher R.; Bourlés D.L.; Brown E.T.; Carretier S. (My University, 2006)
This paper presents an updated synthesis of morphotectonic studies that quantify active tectonics along the Gurvan Bogd mountain range in the Mongolian Gobi-Altay, the site of one of the strongest historic intracontinental earthquakes (Mw 8.1) in 1957. Our goal was to determine the slip rate along the constituent fault segments and to estimate the return period of such large events. Along each segment, cumulative offsets were estimated from topographic surveys, and the ages of the offset markers were determined using cosmic-ray exposure dating. In this review, we reevaluate 10Be data reported in previous publications using a chi-square inversion analysis of depth profiles and an updated scaling model for spatial production rate variations. We also discuss sampling strategies for dating alluvial fans in arid settings.